Research on dynamic modeling and control strategy of motor driven operating mechanism for 126 kV high voltage vacuum circuit breaker - Yifei Wang; Jianyuan Xu; Wei Li; Jinming Liu (Scientific Reports)
Abstract To mitigate the effects of motor load torque variations on the control performance of a 126 kV high voltage vacuum circuit breaker equipped with a motor driven operating mechanism, this paper presents the derivation of dynamic equations for the motor load torque. These equations, formulated using the Euler-Lagrange equation, Lagrange multipliers, and geometric constraints, are expressed in terms of a single independent variable: the angular displacement of the motor. Utilizing these equations, the load torque can be calculated in real-time using the motor position sensor feedback, and the motor control strategy is optimized through a feedforward method designed to actively compensate for load disturbances. Subsequently, an angular displacement trajectory has been designed to serve as a positional reference for the motor control, with the aim of enhancing the operational reliability of the operating mechanism. Furthermore, comparative control experiments have been conducted in the motor-breaker integrated experimental platform to assess the reduction in the motor’s position tracking error, contact bouncing duration, and mechanical collision duration under the optimized motor control strategy. The obtained experimental results reveal the efficacy of the load torque dynamic equations established and their contribution to enhancing control accuracy and improving the operational reliability of the operating mechanism.